STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AKHLAKUL KARIMAH PESERTA DIDIK DI SEKOLAH MENENGAH PERTAMA NEGERI 5 KOTA JAMBI - Rahmi, Alfia; Idarianty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the strategies used by Islamic Religious Education teachers to foster good morals in students at SMPN 5 Jambi City, and to determine whether these strategies have a positive impact on students' morals. This study uses a qualitative research method that focuses on the author's direct observations and structured interviews. The procedure in this study begins with determining the research focus, where the researcher establishes the problem based on facts that occurred during initial observations in the classroom while the Islamic Religious Education teacher was teaching, as well as based on daily interactions between individual students or between students and the teacher. The Islamic Religious Education teacher has implemented a program for his students to foster good morals in students.